2018
DOI: 10.3389/fphar.2017.00975
|View full text |Cite
|
Sign up to set email alerts
|

Scutellarin Suppresses NLRP3 Inflammasome Activation in Macrophages and Protects Mice against Bacterial Sepsis

Abstract: The NLRP3 inflammasome plays a critical role in mediating the innate immune defense against pathogenic infections, but aberrant activation of NLRP3 inflammasome has been linked to a variety of inflammatory diseases. Thus targeting the NLRP3 inflammasome represents a promising therapeutic for the treatment of such diseases. Scutellarin is a flavonoid isolated from Erigeron breviscapus (Vant.) Hand.-Mazz. and has been reported to exhibit potent anti-inflammatory activities, but the underlying mechanism is only p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 72 publications
4
53
0
Order By: Relevance
“…Inflammasome such as Nod‐like receptor pyrin domain‐containing protein 3 (NLRP3) is a cytoplasmic multiportion complex of the innate immune system (Hao et al, ) that leads to maturation and production of cytokines such as IL‐18, IL‐1β, and pyroptosis (lytic host cell death; Liu, Jing, et al, ; Luo et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammasome such as Nod‐like receptor pyrin domain‐containing protein 3 (NLRP3) is a cytoplasmic multiportion complex of the innate immune system (Hao et al, ) that leads to maturation and production of cytokines such as IL‐18, IL‐1β, and pyroptosis (lytic host cell death; Liu, Jing, et al, ; Luo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammasome such as Nod-like receptor pyrin domain-containing protein 3 (NLRP3) is a cytoplasmic multiportion complex of the innate immune system (Hao et al, 2017) that leads to maturation and production of cytokines such as IL-18, IL-1β, and pyroptosis (lytic host cell death; Liu, Jing, et al, 2018;Luo et al, 2014). Gong et al (2015) have studied the effect of curcumin on treated murine macrophage cell line J774A with septic shock and reported that curcumin inhibited the Nod-like receptor pyrin domain-containing protein 3 inflammasome activators significantly, consequently decreased the level of activated caspase-1, which leads to a decrease in IL-1 β secretion as well as improves the condition of illness caused by endotoxic shock.…”
Section: Inhibition Of Nod-like Receptor Pyrin Domaincontaining Promentioning
confidence: 99%
“…Once activation is triggered, NLRP3 recruits downstream apoptosis‐associated speck‐like protein contaiining a CARD, cysteine protease caspase‐1 and then assembles NLRP3 inflammasome complex . Subsequently, caspase‐1 precursor (pro‐caspase‐1) is activated into Cleaved caspase‐1 with the formation of p10 and p20 . Meanwhile, active caspase‐1 converts the cytokines pro‐IL‐1β and pro‐IL‐18 into mature and biologically active IL‐1β and IL‐18, triggering the inflammation occurrence .…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] Subsequently, caspase-1 precursor (pro-caspase-1) is activated into Cleaved caspase-1 with the formation of p10 and p20. [16][17][18] Meanwhile, active caspase-1 converts the cytokines pro-IL-1β and pro-IL-18 into mature and biologically active IL-1β and IL-18, triggering the inflammation occurrence. 19,20 Thus, the assembly of NLRP3 inflammasome, the induction of Cleaved caspase-1 and Cleaved IL-1β are regarded as the important symbols of NLRP3 inflammasome activation.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the compounds whose contents in the decoction were above 100 μg g −1 crude drug included orientin, 2″-O-β-l-galactopyranosylorientin, puerarin, trollisin I, rosmarinic acid, 2″-O-(2′″-methylbutanoyl) isoswertisin, daidzin, scutellarin, 3′-methoxy puerarin, vitexin, 3′-hydroxy puerarin, 2″-O-(2′″-methylbutanoyl) vitexin, kaempferol, caffeic acid, 3,4-dimethoxybenzoic acid, and cynaroside in descending order. These components are mainly from Flos Trollii, Radix Puerariae Lobatae, and Folium Perillae [15][16][17], and have related bioactivities such as antiviral, antibacterial and anti-inflammatory effects [12,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Therefore, these compounds can be considered as the major components of JD.…”
Section: Discussionmentioning
confidence: 99%